PERILAKU KEPEMIMPINAN, MOTIVASI KERJA DAN KINERJA - Febri Yuliani, Abukari, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Leadership Behavior, Work Motivation and Performance. The purpose of this study was to determine and analyze the influence of leadership behavior and work motivation of school principals with teacher performance in State Junior High Schools in Tambang District, Kampar Regency. This research was conducted on teachers at State Junior High Schools who served in Tambang District with a population of 262 teachers, consisting of 7 schools with a sample of 149 teachers. This research is quantitative research. Data collection techniques are interviews, and documentation. Analysis of multiple regression data. The results showed that the leadership behavior and work motivation of school principals had a significant effect on the performance of teachers in state junior high schools in Tambang Subdistrict, Kampar District, with a percentage of 65.2% and the remaining 34.8% influenced by other variables not included in this regression model. Based on linear regression Y = 62,690 + 0,131 Leadership Behavior + 0,444 Work Motivation + e shows that the variable that most influences on teacher performance is work motivation variable which is 60.7% and leadership behavior variable is only 57.6%.